2016
DOI: 10.1177/1753193415625404
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in carpal tunnel relative cross-sectional area: a possible causative factor in idiopathic carpal tunnel syndrome

Abstract: V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 13 publications
1
24
0
3
Order By: Relevance
“…This sex difference was still valid with the normalization of carpal arch area with respect to wrist size to control the potential confounding factor that females tend to have a smaller wrist. Previous studies have shown that women have smaller carpal tunnel cross-sectional area compared to men at both distal and proximal ends of the tunnel [3, 4]. Our study extended the previous findings of smaller carpal tunnel area in women compared to men as reported to the sex-related differences in carpal arch.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This sex difference was still valid with the normalization of carpal arch area with respect to wrist size to control the potential confounding factor that females tend to have a smaller wrist. Previous studies have shown that women have smaller carpal tunnel cross-sectional area compared to men at both distal and proximal ends of the tunnel [3, 4]. Our study extended the previous findings of smaller carpal tunnel area in women compared to men as reported to the sex-related differences in carpal arch.…”
Section: Discussionsupporting
confidence: 89%
“…One possible cause proposed for the higher incidence is that women have a smaller wrist size than men [2]. The smaller wrist size in women also correlates with a relatively smaller carpal tunnel cross-sectional area in women compared to men [3, 4]. However, there were no sex-related differences in the relative carpal tunnel contents area [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…7 , 8) This study demonstrates the changes in the median nerve among only young male participants. In comparison, carpal tunnel volume of female individuals is smaller than that of male individuals, 44) which may affect the deformation of the median nerve after keyboard typing. Therefore, further investigations among female individuals are needed to understand the impact of keyboard typing across different age groups among female individuals.…”
Section: Discussionmentioning
confidence: 96%
“…11 This can be explained by the fact that women have a lower size cuff 12 and lower carpal tunnel elasticity, which can contribute to lower compliance and accommodation of structures. 13,14 It is possible that women are predisposed to more rectified tunnels, which may also contribute to the development of CTS. 15 Based on these publications, our work is in agreement with the literature, with a high prevalence of CTS involvement in women.…”
Section: Discussionmentioning
confidence: 99%